Accelerating Digital Transformation in the Healthcare Sector Through Health Worker Empowerment - Surya, Nella Tri; Gita, Anggi Putri Aria; Pujilestari, Agustina (Jurnal IPTEK Bagi Masyarakat, 2025)
The advancement of digital technology drives transformation across sectors, including healthcare. However, implementation at the primary care level still faces challenges, as seen at Nusukan Health Center in Surakarta City. This community service activity aims to evaluate the success of digital health transformation through health worker empowerment, particularly in utilizing the Healthy Family Application under the PIS-PK program. Methods used include field observations, interviews, and technical training. Results show that despite prior training and data collection, barriers persist such as miscommunication among staff, task delegation, and delays in updating the Healthy Family Index (IKS). Organizational structure and workload also influence the effectiveness of application use. Empowering health workers through training and role-appropriate task distribution is key to supporting digital transformation.